Analysis of micro-doppler characteristics of pedestrians using multiple-input multiple-output (MIMO) radar for enhanced target detection / Shafinaz Mohd Basir - Mohd Basir, Shafinaz (2017)
This paper presents a study on micro-Doppler characteristics of pedestrians using multiple -input multiple-ouput (MIMO) radar designed for automotive radar applications. The signal reflected might be similar in terms of reflecting angle and Doppler spread, between pedestrian and slow moving object.